Iron oxide nanoparticles protected by NIR-active multidentate-polymers as multifunctional nanoprobes for NIRF/PA/MR trimodal imaging. Issue 2 (14th December 2015) - Wu, Yayun; Gao, Duyang; Zhang, Pengfei; Li, Chuansheng; Wan, Qian; Chen, Chi; Gong, Ping; Gao, Guanhui; Sheng, Zonghai; Cai, Lintao
Abstract : Compact NIR-active iron oxide nanoparticles protected by near-infrared catechol-multidentate polymers for NIRF/PA/MR trimodal imaging. Abstract : We designed and synthesized new kinds of near-infrared catechol-based multidentate polymers which were intended to yield compact NIR-active iron oxide nanoparticles with excellent stability and biocompatibility. The resulted multifunctional nanoprobes showed great potential as multimodal contrast agents for NIRF/PA/MR trimodal imaging in vivo .